Recent Development of Studies on Educational Assessment Tools for Children with Autism Spectrum Disorders - Xiaojuan SHA; Weixin HUANG (康复学报)
This paper summarized the recent studies of educational assessment tools for children with autism spectrum disorders, with an analysis of the present application as well as the future developments. Especially, this paper mainly focused on the comparative analysis of"psycho-educational profile", "autistic children development assessment"as well as"Shuangxi rating scale", analyzing their advantages, disadvantages and applicability. Among which, the psycho-educational profile was frequently used as a functional assessment tool for the individualize assessment of children with autism spectrum disorders or related developmental disorder, which could test the current level of the children's capacities and show the features and degree that they diverged from the normal development. While the autistic children development assessment, mainly based on the period of the children development, was usually used as a developmental assessment tool, which could provide a report on the present development and rehabilitative needs of the autistic children as well as an individualized reference for their education and rehabilitation. Finally, the Shuangxi rating scale was applied to assess the developmental level of seven fields of the children's abilities, which turned out to be a developmental and functional assessment tool. It seemed that the educational assessments have played an important role in individualized educational plan for children with autism spectrum disorders, which would contribute to promote the development of their capacities.